Thermo field hydrodynamic and kinetic equations of dense quantum nuclear systems - Tokarchuk, M.V.; Arimitsu, T.; Kobryn, A.E. (Condensed Matter Physics, 1998)
Basic equations of nonequilibrium thermo field dynamics of dense quantum systems are presented. A formulation of nonequilibrium thermo field
dynamics has been performed using the nonequilibrium statistical operator
method by D.N.Zubarev. Hydrodynamic equations have been obtained in
thermo field representation. Two levels of the description of kinetics and
hydrodynamics of a dense nuclear matter are considered. The first one is
a quantum system with strongly coupled states, the second one is a quark-gluon plasma. Generalized transfer equations of a consistent description of
kinetics and hydrodynamics have been obtained, as well as limiting cases are considered. Представлено основні рівняння нерівноважної термопольової динаміки густих квантових систем. Формулювання нерівноважної термопольової динаміки подано методом нерівноважного статистичного
оператора Д.М.Зубарєва. Отримано рівняння гідродинаміки у термопольовому представленні. Розглянуто два рівні опису кінетики та
гідродинаміки густої ядерної матерії: квантові системи сильно зв’язаних станів та кварк-глюонна плазма. Для цих систем отримано узагальнені рівняння переносу узгодженого опису кінетики та гідродинаміки. Розглянуто граничні випадки.